The Effectiveness of Using Quizizz in Improving Learners' Motivation and Engagement in Learning - Heriyanto, Heriyanto; Cahyadi, Achmad; Suroso, Jarot S (STMIK Widya Cipta Dharma, 2024)
This research aims to evaluate the effectiveness of using Quizizz in enhancing learners' motivation and engagement in the learning process. The study seeks to provide educators with insights into the benefits and positive impacts of incorporating gamification in teaching. The materials for this study include academic journal literature related to the use of Quizizz in education. Literature sources were obtained from academic databases such as Google Scholar and Mendeley. This research is limited to literature published within the last five years to ensure the relevance and currency of the findings. It focuses on studies discussing the use of Quizizz in educational contexts. Based on the analysis of several studies, it can be concluded that Quizizz effectively enhances students' motivation and engagement in learning.